Sustainability awareness in the Portuguese wine industry: a grounded theory approach - Ana Trigo; Rui Fragoso; Ana Marta-Costa (International Journal of Agricultural Sustainability, 2022)
In order to bridge the knowledge-gap between sustainability awareness and the old world winegrowing culture, this research explores and analyses perceptions of key individuals in Portuguese wine industry regarding sustainability issues, uncovering intercultural trends, expectations and tensions. A grounded theory approach was used on collected nationwide data from semi-structured interviews with leading wine specialists. After conducting an inductive qualitative-content analysis using IRAMUTEQ software, results displayed key domains of concern rooted into three lexical macro ramifications analogous to the environmental-social-governance factors. The sector’s tendency to approach sustainability based on different strategies of action was also exposed. These are the fuse of two main strategic profiles: impact assessment versus value creation; with external exposure versus inward orientation approach. Findings may be used as a reference to wine managers and policy-makers pursuing sustainability goals. The development of a sustainability framework with guidelines is also recommended for standardized accounting and valuation principles in line with the Portuguese context.